Student Learning on Healthy Heart Gymnastics at State Senior High School 1, Rejang Lebong Regency - Shinta Afrilia Handayani (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the level of student interest in healthy heart exercise in class X students at SMA Negeri 1 Rejang Lebong Regency. This study used a questionnaire or questionnaire format instrument. The population in this study were students of SMA Negeri 1 Rejang Lebong Regency and the sample was class X, amounting to 31 people. In this case, when taking data using a student questionnaire, 10 questions were given. Based on the results of the data taken, the level of interest in learning gymnastics at SMA Negeri 1 Rejang Lebong Regency was 50% enthusiastic and 50% less enthusiastic about participating in healthy heart exercise activities.